(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
ABSTRACT The purpose of this paper is to study the possibility of promoting wooden furniture for houses and offices, coming from sustainable managed forests, in order to support Indian enterprises and the Institutions of the Indian wooden furniture for houses and offices involved by applying effective green marketing methods. This research design is based on a prototype structured questionnaire, according to objective of the research, 55 responses were collected from Indian wooden furniture stores for houses and offices, enterprises in 2012. The questionnaires were analyzed with the statistical program SPSS, using descriptive statistics and correlation analysis. The main aim was the investigation of use, knowledge and promotion of wooden furniture for houses and offices that emanates from forests that are under sustainable management, and thus planning the green marketing of these products. The Indian enterprises of the wooden furniture for houses and offices expressed a great concern for the protection of forests. Majority strongly supports the certification of a sustainable management of Indian forests. The enterprises believe that the movement of green buildings moves with a slow pace and forecast that eco consumers are prone to offer an additional of around 6% on price in order to buy wooden furniture for houses and offices. A high percent of most Institutions of Education promote that they use wooden furniture for houses, hostels and offices, and propose their image building through newspapers, magazines, Internet portals, websites, etc of high approach. This research study discusses reflections and forecasts on the growth of this new market of wooden furniture for houses and offices. It offers valuable insights on the market of wooden furniture for houses and offices, and also future developments in the coming years, which can support both enterprises and the institutions involved in strategy forming and decision making, to surmount an important share of the market of eco consumers. The study also proposes an effective method of eco marketing applications.